Mucus-responsive functionalized emulsions: design, synthesis and study of novel branched polymers as functional emulsifiers. Issue 51 (18th August 2020) - Edwards, Stephanie E.; Flynn, Sean; Hobson, James J.; Chambon, Pierre; Cauldbeck, Helen; Rannard, Steve P.
Abstract : Mucoadhesion and mucus-sensitive materials have many applications. Redundant chain-ends within branched polymer emulsifiers have been functionalized with thiols, without compromising emulsion stability, to create mucus-interacting emulsions. Abstract : Mucus lines the moist cavities throughout the body, acting as barrier by protecting the underlying cells against the external environment, but it also hinders the permeation of drugs and drug delivery systems. As the rate of diffusion is low, the development of a system which could increase retention time at the mucosal surface would prove beneficial. Here, we have designed a range of branched copolymers to act as functional mucus-responsive oil-in-water emulsifiers comprising the hydrophilic monomer oligo(ethylene glycol) methacrylate and a hydrophobic dodecyl initiator. The study aimed to investigate the importance of chain end functionality on successful emulsion formation, by systematically replacing a fraction of the hydrophobic chain ends with a secondary poly(ethylene glycol) based hydrophilic initiator in a mixed-initiation strategy; a decrease of up to 75 mole percent of hydrophobic chain ends within the branched polymer emulsifiers was shown to maintain comparative emulsion stability. These redundant chain ends allowed for functionality to be incorporated into the polymers via a xanthate based initiator containing a masked thiol group; thiol groups are known to have mucoadhesive character, due to their ability to form disulfide bonds with the cysteine rich areas of mucus. The mucoadhesive nature of emulsions stabilised by thiol-containing branched copolymers was compared to non-functional emulsions in the presence of a biosimilar mucosal substrate and enhanced adherence to the mucosal surface was observed. Importantly, droplet rupture and mucus triggered release of dye-containing oil was seen from previously highly-stable thiol-functional emulsions; this observation was not mirrored by non-functional emulsions where droplet integrity was maintained even in the presence of mucus.